2021
DOI: 10.1158/0008-5472.can-20-2960
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ATM Induces Hypersensitivity to Proton Irradiation by Upregulating Toxic End Joining

Abstract: Proton Bragg peak irradiation has a higher ionizing density than conventional photon irradiation or the entrance of the proton beam profile. Whether targeting the DNA damage response could enhance vulnerability to the distinct pattern of damage induced by proton Bragg peak irradiation is currently unknown. Here we performed genetic or pharmacologic manipulation of key DNA damage response elements and evaluated DNA damage signaling, DNA repair, and tumor control in cell lines and xenografts treated with the sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Studies in vitro have demonstrated proton radiation-induced DNA double strand breaks (DSBs) to be preferentially repaired by homologous recombination (HR), one of the major DNA repair pathways in DNA-damage response [40][41][42][43]. In a recent in vivo study, tumours with HR deficiency due to BRCA1 mutations display an increased radiosensitivity in the Bragg peak as compared to photon radiation, and thereby an increased RBE compared to tumours with a functional HR pathway is expected [44]. These findings point towards the possibility of selecting specifically proton radiosensitive tumours for proton therapy.…”
Section: Preclinical Foundationmentioning
confidence: 99%
“…Studies in vitro have demonstrated proton radiation-induced DNA double strand breaks (DSBs) to be preferentially repaired by homologous recombination (HR), one of the major DNA repair pathways in DNA-damage response [40][41][42][43]. In a recent in vivo study, tumours with HR deficiency due to BRCA1 mutations display an increased radiosensitivity in the Bragg peak as compared to photon radiation, and thereby an increased RBE compared to tumours with a functional HR pathway is expected [44]. These findings point towards the possibility of selecting specifically proton radiosensitive tumours for proton therapy.…”
Section: Preclinical Foundationmentioning
confidence: 99%
“…In terms of PBT, it has been shown that U2OS and BT549 cells irradiated at the Bragg peak with a higher RBE upregulate utilization of HR, but interestingly that inhibiting ATM redirected cells to the NHEJ pathway leading to the formation of toxic DSB repair end products. 67 This evidence was replicated in an in vivo xenograft model, in which inhibiting ATM in combination with PBT was shown to significantly delay tumor growth, and that Bragg peak protons were furthermore highly effective in the killing of HR-defective (BRCA-1 deficient) cells and tumors. 67 Such findings suggest that cells may switch between different repair pathways when repairing more complex DSBs induced by high-LET radiations.…”
Section: Alternative Radiotherapy Treatments For Gbmmentioning
confidence: 80%
“…Overall, 40% of antigenic CTL-tumor cell interactions cause DNA damage-associated repair foci in the nucleus, which are associated with death at ~30% probability; alternatively, DNA damage-associated foci are reversible (within hours) followed by tumor cell survival [13]. Due to its central role in securing tumor cell survival and emerging resistance, the DNA damage response (DDR) is considered an important target for improving combinations of chemo-, radio-and molecular therapy, for example, by ATM/ATR and poly(ADP-ribose) polymerase (PARP) inhibitors [30][31][32][33].…”
Section: Trends Trends In In Cancer Cancermentioning
confidence: 99%